2013
DOI: 10.12772/tse.2013.50.132
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Chitosan/Poly(vinyl alcohol) Nanofibers Containing Silver Zeolite

Abstract: Non-toxic, biodegradable, and biocompatible chitosan/poly(vinyl alcohol)(PVA) nanofibers were prepared by electrospinning. The nanofibers were prepared with the following weight composition ratios:100:0 (PVA homopolymer), 90:10, 80:20, and 70:30. To improve their antibacterial activity, the nanofibers were prepared with silver zeolite nanoparticles. The properties of the nanofibers at various blend ratios were investigated by differential scanning calorimetry (DSC), Fourier transform infrared (FTIR) spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…These effects might be caused by interface incompatibility and a defective nanocomposite structure. Llorens et al 2012 reported similar defects in the distribution of silver zeolites in polylactide, together with voids growing around the permutate [ 35 ]. These results indicate that the composite antimicrobial particles were still acceptably well dispersed in the ethyl cellulose layer.…”
Section: Resultsmentioning
confidence: 99%
“…These effects might be caused by interface incompatibility and a defective nanocomposite structure. Llorens et al 2012 reported similar defects in the distribution of silver zeolites in polylactide, together with voids growing around the permutate [ 35 ]. These results indicate that the composite antimicrobial particles were still acceptably well dispersed in the ethyl cellulose layer.…”
Section: Resultsmentioning
confidence: 99%
“…또한 Ag의 단독 사용 뿐만 아니라 제올라이트 등에 함침 된 형태 [23][24][25][26][27]도 직물에 적용되고 있다. 은-제올라이트의 조합은 금속으로서의 은 원자 단독 사용시보다 더 뛰어난 향균성을 나타내고 열적 안전성도 훌륭하다 [28]. 그러나 그 메커니즘이 정확히 밝혀지지는 않았지만 항균성 발휘에 있 어서 용존산소가 반드시 필요하기 때문에 [27], 아웃도어와 같이 땀, 우천, 먼지로 인해 오염이 빈번한 적용분야에서는 항균력 발휘에 한계가 있다.…”
Section: 한국섬유공학회지 제50권 제5호 2013년unclassified